Functional analyses and prognostic significance of SFRP1 expression in bladder cancer - Rogler, Anja; Kendziorra, Emil; Giedl, Josef; Stoehr, Christine; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; Stoehr, Robert (Journal of Cancer Research and Clinical Oncology, 2015)
We previously showed that the Wnt-signaling antagonist SFRP1 (secreted frizzled-related protein 1) is a promising marker in bladder cancer. The aim of this study was to validate the prognostic role and analyze the functional significance of SFRP1.Four bladder cancer cell lines (RT112, RT4, J82 and BFTC905) and one urothelial cell line (UROtsa) were used for functional characterization of SFRP1 expression. Effects on viability, proliferation and wound healing were investigated, and canonical Wnt-pathway activity as well as Wnt-signaling target gene expression was analyzed. Additionally, tissue micro-arrays from two different bladder tumor cohorts were evaluated for SFRP1 expression, and associations with survival and histopathological parameters were analyzed.The cell lines RT112, RT4, J82 and UROtsa showed SFRP1 expression. In BFTC905, SFRP1 expression was inhibited by promoter hypermethylation. Wnt-pathway activity was absent in all cell lines and independent from SFRP1 expression. RT112 and BFTC905 were used for further functional characterization. SFRP1 overexpression resulted in decreased viability and migration in BFTC905 cells. Knockdown of SFRP1 expression in RT112 cells resulted only in marginal effects. In bladder tumors, SFRP1 expression was associated with lower tumor grade, but not with progression in patients with papillary bladder cancer. SFRP1 expressing papillary bladder cancer tumors also demonstrated a tendency to longer overall survival.SFRP1 is reducing malignant potential of BFTC905 cells, but not by regulation of canonical Wnt-signaling pathway. Other pathways, like non-canonical Wnt or the MAPK pathway, could be activated via SFRP1-expression loss. In bladder tumors, SFRP1 has the potential to predict outcome for a subset of papillary bladder tumors.
EVALuna2:6533